2010
DOI: 10.1002/ijc.25082
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase of regenerating liver‐3 as a convergent therapeutic target for lymph node metastasis in esophageal squamous cell carcinoma

Abstract: Phosphatase of regenerating liver-3 (PRL-3) is a molecule associated with metastasis in a diverse of cancers, which, however, remains largely unknown in esophageal squamous cell carcinoma (ESCC). We examined both the clinical significance of PRL-3 expression and its biological roles, and assessed possibilities as a therapeutic target in ESCC. PRL-3 expression was found in 78% (69 of 88) of the primary ESCC on immunohistochemistry; it was the strong independent predictor for lymph node metastasis (LNM) on a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 36 publications
5
38
0
Order By: Relevance
“…35 In this study, it was confirmed using U-0126 (an ERK inhibitor) and LY-294002 (a PI3K inhibitor) that PRL-3 upregulated the expression of MMP-7 through these oncogenic signaling pathways. The results suggest that the PI3K/AKT and ERK pathways are involved in the induction of MMP-7 by PRL-3.…”
Section: Discussionsupporting
confidence: 54%
“…35 In this study, it was confirmed using U-0126 (an ERK inhibitor) and LY-294002 (a PI3K inhibitor) that PRL-3 upregulated the expression of MMP-7 through these oncogenic signaling pathways. The results suggest that the PI3K/AKT and ERK pathways are involved in the induction of MMP-7 by PRL-3.…”
Section: Discussionsupporting
confidence: 54%
“…66 The molecule was initially believed to be involved in distant metastasis of colorectal cancer, but subsequent research has revealed that PRL-3 plays a causative role in lymph node metastasis in diverse cancers, including gastric cancers. 67-77 PRL-3 is a tyrosine phosphatase that is needed for cancer invasion, motility, and metastasis [77][78][79] as well as angiogenesis, 80 which may be regulated by dephosphorylation of several molecules, such as integrins, 81,82 Ezrin, 83 or cadherin. 84 We recently demonstrated that a PRL-3 inhibitor (1,4-bromo-2-benzylidene rhodamine) dramatically suppressed the metastatic capacity in cell lines with PRL-3 overexpression, irrespective of the DNA amplifi cation status in esophageal cancer.…”
Section: Apc K-ras P53 and Prl-3 Alterations In Gastric Cancer Cormentioning
confidence: 99%
“…Immunohistochemistry was carried out using the anti-HOPX polyclonal antibody (dilution of 1:100), as described previously (Ooki et al, 2009). As HOPX immunoreactive scoring algorithms had not been optimized and standardized, the expression status was assessed using a German scoring system (Supplementary Table 5) (Remmele and Stegner, 1987).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Anchorage-independent cell growth assay was carried out as described previously (Ooki et al, 2009). Cells were fed weekly by overlying fresh soft-agar solution containing G418, and colonies were photographed after 2 weeks of incubation.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation